(untitled) (Journal of the College of Basic Education, 2022)
The present study aimed at conducting a comparative study between the old and modern methods of the mathematics book for the intermediate stage in Iraq. To reach the objectives of the study, a sample of the two methods was taken for the first grade. The two methods were compared according to the components of mathematical knowledge and the differences and similarities between the subjects. The study aims to complete the indicators of the unrealized standards in the books of modern mathematics and add the important topics.